DAMPAK DAN PENGARUH PENETAPAN DESA WISATA PANTAI ANYER TERHADAP KONDISI SOSIAL, EKONOMI, DAN LINGKUNGAN MASYARAKAT (Studi Di Desa Kamasan Kecamatan Cinangka Kabupaten Serang) - Ribawati, Eko (Universitas Sultan Ageng Tirtayasa, 2022)
The development of tourist villages has now become an alternative to local economic development thathas been applied I various regions. One of the areas developed as a tourist village is Kamasan Village.This village is located in Cinangka District, Serang Regency, Province Banten, which is part of theAnyer Beach tourist village area. Kamasan Village has the potential to be development because itsclose to Anyer Beach tourist area. In addition, in this village there are some that have a strongattraction to tourists and allow them to become superior objects, for example related to agro potential.This tourism activity opens up economic opportunities so that it greatly affects the income that can befelt by the community. Based on the result of the study, coastal-based tourism in Kamasan PantaiAnyer Village still needs to be directed to tourism development strategies and policies by consideringthe environmental, social, and cultural potential of the local community. The current coastal-basedtourism management is still in a simple structure. In addition to the economic potential, of course,there are negative impacts from the existence of tourism itself, incluiding environmental and socialimpacts. The accumulation of garbage is a scourge and a problem that has not been resolved until nowas well as changes in people's lifestyles which tend to be negative, of course. Therefore, there is a needfor cooperation from the local government which is not only in the form of fund, but also more incommunity empowerment activities.